Social values as arguments: similar is convincing - Maio, Gregory R.; Hahn, Ulrike; Frost, John-Mark; Kuppens, Toon; Rehman, Nadia; Kamble, Shanmukh (Frontiers in Psychology, 2014)
Politicians, philosophers, and rhetors engage in co-value argumentation: appealing to one value in order to support another value (e.g., “equality leads to freedom”). Across four experiments in the United Kingdom and India, we found that the psychological relatedness of values affects the persuasiveness of the arguments that bind them. Experiment 1 found that participants were more persuaded by arguments citing values that fulfilled similar motives than by arguments citing opposing values. Experiments 2 and 3 replicated this result using a wider variety of values, while finding that the effect is stronger among people higher in need for cognition and that the effect is mediated by the greater plausibility of co-value arguments that link motivationally compatible values. Experiment 4 extended the effect to real-world arguments taken from political propaganda and replicated the mediating effect of argument plausibility. The findings highlight the importance of value relatedness in argument persuasiveness.